Undergraduate nursing students' experiences of humor in the classroom - Ahern, Tracy R. (My University, 2009)
The pedagogical use of humor has been shown to have both psychological and physiological effects on learners. The use of humor in teaching has been linked to learning in several quantitative studies, however qualitative research on humor in nursing education is significantly under-represented. The purpose of this qualitative, descriptive study, therefore, is to explore students' experiences of humor in the classroom. A phenomenological approach will be taken as a framework for the study. A volunteer sample of 10 undergraduate students from a four year university in Wisconsin will participate in the study. Data will be collected using an semi-structured interview utilizing four open-ended interview questions: (a) Describe an experience when humor was utilized in the classroom in a positive manner, (b) Describe an experience when humor was used in the classroom in a negative manner, (c) Describe an event in which humor did or did not facilitate in your learning and why, (d) Describe humor as you have experienced it in the classroom. Interviews will be audio-taped and transcribed verbatim. Data will be analyzed for emerging themes. By identifying themes from within stories and across stories a shared experience of humor will obtained thus allowing for the integration of subjective perspectives of research participants.
A clinical paper submitted in partial fulfillment of the requirements for the degree of Master of Science in Nursing Educator
Keywords: communication in education, humor in education, nursing students' attitudes, nursing - study and teaching